2019
DOI: 10.1111/grs.12253
|View full text |Cite
|
Sign up to set email alerts
|

Causality of climate and soil factors affecting whole crop rye (Secale cereale L.) yield as part of natural ecosystem structure via longitudinal structural equation model in the Republic of Korea

Abstract: In this study, the causality of climate and soil factors affecting the whole crop rye yield was identified via structural equation model, such as the seasonal effect between autumn and next spring, the indirect effect of the precipitation and the relationship between soil physical and climate factors. To identify the causality under the part of natural ecosystem, the structure was modeled with climates (autumnal accumulated temperature, autumnal growing days, spring accumulated temperature, spring growing days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Therefore, we concluded that the precipitation effect on yield was effective based on sufficient temperature in the spring (14.18°C or more, at least 7.42°C or more). According to Kim et al [23], the yield increased with increasing temperature, and the effect of precipitation on yields fluctuated significantly only at high temperature. The optimum growing temperature was in the range of 15°C–18°C, and IRG could maintain growth down to 4°C [29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we concluded that the precipitation effect on yield was effective based on sufficient temperature in the spring (14.18°C or more, at least 7.42°C or more). According to Kim et al [23], the yield increased with increasing temperature, and the effect of precipitation on yields fluctuated significantly only at high temperature. The optimum growing temperature was in the range of 15°C–18°C, and IRG could maintain growth down to 4°C [29].…”
Section: Resultsmentioning
confidence: 99%
“…The climate information from the prototyped IRG model could be used as good prior information in cases of a small sample of cool-season forage crops. Causality of both climatic and soil factors on yield were identified initially by SEM for whole crop rye ( Secale cereale L.) [23]. They found that the variation of precipitation was significally effective under the range of high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…This clear tendency was, therefore, certain to reflect both direct and indirect effects on yield in the upland fields. According to Kim et al [17], the fluctuation of precipitation effect on DMY of whole crop rye increased at daily mean temperatures above 8 • C, which means that precipitation affected yield at appropriate temperatures.…”
Section: Cultivation Suitability Classification Between Upland and Pamentioning
confidence: 99%
“…In the Republic of Korea, IRG has mainly been cultivated in paddy fields under the rice-rotation system, accounting for 81.4% of the total IRG cultivation areas (21,700 ha) in 2007 [3,4]. IRG utilization has expanded gradually to 56.3% of the total area used for forage production, and the area is restricted temperature was less relevant [17]. However, these studies did not take into account the field types closely related to climate, soil, and cultivation techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation